Five-Year results of a multi-specialty induction course for surgical training - Kwan, Jing Yi; Lainas, Panagiotis; Banks, Philippa; Jimenez De Veciana, Anna; Said, Hagar; Mehrem, Anna; Debbarma, Manash; Matthews, Melissa; Etim, Gloria; Biyani, Chandra Shekhar; Rajpal, Sanjay; Phillipson, Mark; et al. (Frontiers in Surgery, 2023)
Background: The Essential Surgical Skills Course (ESSC) is a multi-specialty induction ‘boot camp’ style course that has been run successfully for five years. The aim of the current paper is to create an accurate guide for the replication of the course by other teams and assess the course’s fitness for purpose, through the survey feedback provided by trainees. Methods: The course’s fitness for purpose was assessed through cumulative five-year survey feedback from trainees. This observational study describes the design and process of content adjustment according to feedback. Results: The course its five-year span offered twelve different procedural skills in four different specialties. Feedback for each session was persistently >8/10. Key themes identified as beneficial include teacher-to-trainee ratio (often 1:1), teaching style, course structure and responsiveness. Conclusions: The ESSC was found to be fit for purpose for the induction of trainees into surgical training. The key factors contributing to the success of the course include the structured method of curriculum design, outstanding teaching delivery methods, teacher-to-trainee ratio, the availability of appropriate faculty and infrastructure and the willingness to learn from trainee feedback and adjust the content of the course accordingly. It acts as a paradigm for courses aimed to prepare surgical trainees for a ‘step-up’ in their careers.